Bloodstream infections exacerbate incidence and severity of symptomatic glucocorticoid‐induced osteonecrosis. Issue 6 (13th February 2019) - Finch, Emily R.; Janke, Laura J.; Smith, Colton A.; Karol, Seth E.; Pei, Deqing; Cheng, Cheng; Kaste, Sue C.; Inaba, Hiroto; Pui, Ching‐Hon; Wolf, Joshua; Relling, Mary V.
Abstract: Background: Osteonecrosis is a common toxicity associated with glucocorticoid (e.g., dexamethasone and prednisone) treatment of children with acute lymphoblastic leukemia (ALL), but risk factors are incompletely defined. Infections are also a common complication of ALL therapy. Lipopolysaccharide (LPS) is used experimentally to mimic infection‐related systemic effects. To our knowledge, the contribution of systemic infections to the risk of glucocorticoid‐induced osteonecrosis has not been investigated. Procedure: Patients with ALL on St. Jude Total Therapy XV ( n  = 365) were assessed for documented bacteremia prior to development of osteonecrosis, which was confirmed by MRI, and graded using the National Cancer Institute's Common Terminology for Adverse Events (version 3.0). In a preclinical model, Balb/cJ mice treated with dexamethasone plus or minus LPS were assessed for frequency and severity of osteonecrosis and arteriopathy. Results: We found that patients with ALL who experienced bacteremia had a higher frequency of symptomatic osteonecrosis (≥grade 2) than those who did not (OR: 1.88; 95% CI, 1.03–3.41, P  = 0.038). LPS exacerbated experimental dexamethasone‐induced osteonecrosis. Mice treated with dexamethasone plus LPS had a higher incidence of osteonecrosis ( P  = 0.00086) and arteriopathy ( P  = 0.0047) than did those treated with dexamethasone alone, and the severity of osteonecrosis ( P  = 0.00045) and arteriopathy ( P  = 0.0048) was also more pronounced with the addition of LPS treatment. The increase in osteonecrosis was not explained by any alteration of dexamethasone pharmacokinetics by LPS. Conclusions: These data identify systemic infection during ALL therapy as a novel risk factor in the development of glucocorticoid‐induced osteonecrosis.